Front Cover: Formation of Mixed‐Valence Luminescent Silver Clusters via Cation‐Coupled Electron‐Transfer in a Redox‐Active Ionic Crystal Based on a Dawson‐type Polyoxometalate with Closed Pores (Eur. J. Inorg. Chem. 16/2021). Issue 16 (7th April 2021) - Haraguchi, Naoya; Okunaga, Tomoki; Shimoyama, Yuto; Ogiwara, Naoki; Kikkawa, Soichi; Yamazoe, Seiji; Inada, Miki; Tachikawa, Takashi; Uchida, Sayaka
Abstract : The Front Cover shows a redox‐active ionic crystal based on a Dawson‐type polyoxometalate (POM), which can form and stabilize small mixed‐valence luminescent silver clusters via a cation‐coupled electron‐transfer reaction between the reduced POM and Ag + . The silver cluster can stably exist without the aid of protecting ligands at room temperature. X‐ray photoelectron spectroscopy, photoluminescence, and X‐ray absorption fine structure measurements suggest that the silver species exist mainly as [Ag4 ] 2+ in a tetrahedral geometry in the closed pores of the ionic crystal. More information can be found in the Communication by S. Uchida and co‐workers .